Existential Therapy As A Skills-Learning Process (Existential Analysis: Journal of the Society for Existential Analysis, 2016)
This paper suggests that learning skills is radically different from learning techniques. The origin of the difference is primarily that techniques are tools to be used whereas skills are owned ways of being. The way skills become learnt is through a gradual process of understanding of the personal meaning of the activity such that the skill becomes embodied and owned through attention, perseverance and understanding of mistakes, rather than being simply remembered. It is proposed that not only is there a defined way that skills get learnt, embodied, but that life is a process of learning skills, and also that a person's ability to exercise their skills is context sensitive. Suggestions are made for the way a therapist can understand the client's place in the skills-learning process and match their actions and interventions accordingly.
Keywords: Skills; techniques; learning; phenomenology; emotions; responsibility; embodied; perseverance